Contributions of Petri Nets to the Reliability and Availability of an Electrical Power System in a Big European Hospital - A Case Study - Pinto, Constâncio António (2021)
The energy power supply infrastructure of a hospital, to function correctly, needs to be well maintained to ensure its reliability and, by consequence, the maximum integrated availability. In this paper, the authors propose the use of Petri Nets to help the improvement of the electric power system reliability, having as a case study a big European Hospital. The purpose of the research is to identify and analyse the potential failures of the system and to suggest solutions to improve the operations and maintenance to maximise the availability and reliability of those assets through possible and objective answers. It was necessary to develop a diagnosis and planning methodology to assess the reliability of several components of the energy power supply system. It is dynamic modelling based on a block diagram of the system and transposed to representation by Petri Nets. The analysis and the simulation of the discrete events of the system, as well as the visualisation of the process functioning and the communications inside, was made. Additionally, they were referred to other approaches, like the Fuzzy Petri Nets and Stochastic Petri Nets, as well as a future balance about its application in a situation like the analysed in this paper.